(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
One of the neurological complications in patients with juvenile rheumatoid arthritis is a disturbance of psycho-emotional background and cognitive disorders. Due to the lack of a pronounced clinical picture and insufficient awareness in the literature, the topic is topical.